Prevalence, patient characteristics and outcome of hyponatremia in acute heart failure. (3rd October 2022) - Aliyeva, F; Belkin, M; Wussler, D; Kozhuharov, N; Mork, C; Strebel, I; Nowak, A; Papachristou, A; Breidthardt, T; Mueller, C
Abstract: Background: Hyponatremia is the most common electrolyte disturbance found in hospitalized patients. Previous studies have shown that low serum sodium levels at presentation are associated with increased mortality and morbidity in patients hospitalized with acute heart failure (AHF). However, given the complicated multifactorial origin of hyponatremia, the role of serum sodium level in risk stratification in patients with AHF is still largely unknown. Purpose: To evaluate the prevalence and prognostic value of hyponatremia in patients presenting with AHF to the emergency department (ED). Methods: Basics in Acute Shortness of Breath EvaLuation (BASEL V) was a prospective, multicenter, diagnostic study recruiting dyspneic patients at the ED. The final diagnosis of AHF was adjudicated by 2 independent physicians. Hyponatremia was defined as a serum sodium level of <135 mmol/l. The prognostic accuracy of hyponatremia in predicting all-cause mortality and a composite outcome of death and heart failure (HF) rehospitalization was quantified using multivariable adjusted Cox regression. Adjustments were made for the following variables: age, sex, history of ischemic heart disease, previous HF, infection as a trigger of AHF, systolic blood pressure, glomerular filtration rate and log-transformed N-terminal pro-B-type natriuretic peptide (NT-proBNP) at presentation. The incremental value of hyponatremia to the MEESSI-Score, a validated AHF risk score, was quantified using area under the curve (AUC) analyses. Results: Among 1572 patients with AHF, 1499 patients were eligible for the main analysis, of whom 215 (14.3%) had hyponatremia, 1249 (83.3%) normonatremia and 35 (2.3%) hypernatremia at presentation. Of those with hyponatremia, 21 (9.8%) and 54 (25.1%) patients died, 27 (12.6%) and 79 (36.7%) patients experienced the composite outcome within 30 and 180 days, respectively. Multivariable adjusted hazard ratios (aHR) were 0.97 (95%-CI 0.94–1.01) and 0.97 (95%-CI 0.95–0.99) for mortality, 0.97 (95%-CI 0.94–1.00) and 0.98 (95%-CI 0.95–0.99) for the composite outcome within 30 and 180 days, respectively. The risk for mortality and a composite of all-cause mortality and HF rehospitalization within 180 days after presenting to the ED with AHF rose significantly with a lower sodium level at presentation. Each 1-unit decrease in sodium level [mmol/L] was associated with a 3% and 2.7% increase in the hazard rate of mortality (aHR 0.97, p=0.01) and the composite outcome (aHR 0.98, p=0.01), respectively. While in the 30-day analyses after multivariable adjustment sodium had no significant prognostic value. The already excellent predictive ability of the MEESSI-Score for 30-day mortality was not enhanced by sodium level (AUC 0.80 versus 0.80, p=0.834). Conclusion: Hyponatremia at presentation is associated with a higher risk of 180-day mortality in patients with AHF. However, its role as an independent prognostic marker in risk stratification remains unclear. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science FoundationSchweizerische Herzstiftung